Identifying and dismantling racism in Australian perinatal settings: Reframing the narrative from a risk lens to intentionally prioritise connectedness and strengths in providing care to First Nations families. Issue 1 (February 2023) - Hine, Rochelle; Krakouer, Jacynta; Elston, Jacinta; Fredericks, Bronwyn; Hunter, Sue-Anne; Taylor, Karinda; Stephens, Tracey; Couzens, Vicki; Manahan, Esmai; DeSouza, Ruth; Boyle, Jacqueline; Callander, Emily; et al.
Abstract: Introduction: The perinatal period is a time when provision of responsive care offers a life course opportunity for positive change to improve health outcomes for mothers, infants and families. Australian perinatal systems carry the legacy of settler-colonialism, manifesting in racist events and interactions that First Nations parents encounter daily. Objective: The dominance of a western risk lens, and conscious and unconscious bias in the child protection workforce, sustains disproportionately high numbers of First Nations infants being removed from their parents' care. Cascading medical interventions compound existing stressors and magnify health inequities for First Nations women. Design: Critical discourse was informed by Indigenous ways of knowing, being and doing via targeted dialogue with a group of First Nations and non-Indigenous experts in Australian perinatal care who are co-authors on this paper. Dynamic discussion evolved from a series of yarning circles, supplemented by written exchanges and individual yarns as themes were consolidated. Results: First Nations maternity services prioritise self-determination, partnership, strengths and communication and have demonstrated positive outcomes with, and high satisfaction from First Nations women. Mainstream perinatal settings could be significantly enhanced by embracing similar principles and models of care. Conclusions and relevance: The Australian Anti-racism in Perinatal Practice (AAPP) Alliance calls for urgent transformations to Australian perinatal models of care whereby non-Indigenous health policy makers, managers and clinicians take a proactive role in identifying and redressing ethnocentrism, judgemental and culturally blind practices, reframing the risk narrative, embedding strength-based approaches and intentionally prioritising engagement and connectedness within service delivery.